2022
DOI: 10.1136/bmj-2022-073153
|View full text |Cite
|
Sign up to set email alerts
|

Transmission dynamics of monkeypox in the United Kingdom: contact tracing study

Abstract: Objective To analyse the transmission dynamics of the monkeypox outbreak in the UK, declared a Public Health Emergency of International Concern in July 2022. Design Contact tracing study, linking data on case-contact pairs and on probable exposure dates. Setting Case questionnaires from the UK Health Security Agency (UKHSA), United Kingdom. Participants 2746 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 19 publications
3
95
2
4
Order By: Relevance
“…However, seroepidemiological studies in Africa, 3 , 97 and retrospective PCR detection in male sexual health clinic attendees in France 98 and Belgium, 99 suggest that some patients could have an asymptomatic infection, and modelling studies suggest that in the 2022 outbreak approximately half of the transmissions occurred in the pre-symptomatic phase. 100 Further research is needed to determine the potential for transmission from individuals with an asymptomatic infection.…”
Section: Transmissionmentioning
confidence: 99%
“…However, seroepidemiological studies in Africa, 3 , 97 and retrospective PCR detection in male sexual health clinic attendees in France 98 and Belgium, 99 suggest that some patients could have an asymptomatic infection, and modelling studies suggest that in the 2022 outbreak approximately half of the transmissions occurred in the pre-symptomatic phase. 100 Further research is needed to determine the potential for transmission from individuals with an asymptomatic infection.…”
Section: Transmissionmentioning
confidence: 99%
“…In a linked paper, Ward and colleagues (doi:10.1136/bmj-2022-073153) used routine case questionnaires and contact tracing data to estimate two important characteristics of the monkeypox outbreak in the UK: the serial interval and incubation period 3. They found that shorter serial intervals are more common than shorter incubation periods.…”
mentioning
confidence: 99%
“…Knowledge of the serial interval is key, as it informs on the reproduction number and the required intensity of control measures to stop an outbreak. Current estimates of the mean serial interval of monkeypox vary with a recent study estimating the mean serial interval as 5.6 days 4 , while estimates have been reported of 8.5 days in the US 5 , 9.5 days in UK 6 , and 12.5 days in Italy 7 . There is no general consensus on an estimate of mean serial interval for the current monkeypox outbreak, largely due to the limited availability of reliable data.…”
Section: Introductionmentioning
confidence: 72%